Evolution of Mitral Valve Prolapse: Insights From the Framingham Heart Study - Delling, Francesca N.; Rong, Jian; Larson, Martin G.; Lehman, Birgitta; Fuller, Deborah; Osypiuk, Ewa; Stantchev, Plamen; Hackman, Brianne; Manning, Warren J.; Benjamin, Emelia J.; Levine, Robert A.; Vasan, Ramachandran S. (Circulation (New York, N.Y.), 2016)
BACKGROUND—Longitudinal studies of mitral valve prolapse (MVP) progression among unselected individuals in the community, including those with nondiagnostic MVP morphologies (NDMs), are lacking. METHODS AND RESULTS—We measured longitudinal changes in annular diameter, leaflet displacement, thickness, anterior/posterior leaflet projections onto the annulus, coaptation height, and mitral regurgitation jet height in 261 Framingham Offspring participants at examination 5 who had available follow-up imaging 3 to 16 years later. Study participants included MVP (n=63); NDMs, minimal systolic displacement (n=50) and the abnormal anterior coaptation phenotype (n=10, with coaptation height >40% of the annulus similar to posterior MVP); plus 138 healthy referents without MVP or NDMs. At follow-up, individuals with MVP (52% women, 57±11 years) had greater increases of leaflet displacement, thickness, and jet height than referents (all P<0.05). Eleven participants with MVP (17%) had moderate or more severe mitral regurgitation (jet height ≥5 mm) and 5 others (8%) underwent mitral valve repair. Of the individuals with NDM, 8 (80%) participants with abnormal anterior coaptation progressed to posterior MVP; 17 (34%) subjects with minimal systolic displacement were reclassified as either posterior MVP (12) or abnormal anterior coaptation (5). In comparison with the 33 participants with minimal systolic displacement who did not progress, the 17 who progressed had greater leaflet displacement, thickness, coaptation height, and mitral regurgitation jet height (all P<0.05). CONCLUSIONS—NDM may evolve into MVP, highlighting the clinical significance of mild MVP expression. MVP progresses to significant mitral regurgitation over a period of 3 to 16 years in one-fourth of individuals in the community. Changes in mitral leaflet morphology are associated with both NDM and MVP progression.